Endometriosis of the Appendix - Lee, Jin Hyung; Park, Nae Kyeong (Soonchunhyang medical science, 2013)
Endometriosis is a well-recognized gynecological condition in the reproductive age group. Endometriosis of the appendix is an entity of extragonadal endometriosis. The incidence of appendiceal endometriosis is lower than 1% among pathologies of pelvic endometriosis. Women can present with symptoms mimicking acute appendicitis or chronic pelvic pain. Diagnosis can be made only after a histopathological examination following the operation. We report here a case of appendiceal endometriosis, which were operated on for a prediagnosis of acute appendicitis, but postoperatively diagnosed as appendiceal endometriosis. KCI Citation Count: 0